2021
DOI: 10.3390/insects12010054
|View full text |Cite
|
Sign up to set email alerts
|

Pollinators on Cowpea Vigna unguiculata: Implications for Intercropping to Enhance Biodiversity

Abstract: Pollinators are on the decline and loss of flower resources play a major role. This raises concerns regarding production of insect-pollinated crops and therefore food security. There is urgency to mitigate the decline through creation of farming systems that encourage flower-rich habitats. Cowpea is a crop that produces pollen and nectar attractive to pollinators. Twenty-four cowpea varieties were planted, and the number of pollinators were counted using three sampling methods: pan traps, sticky traps, and dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 58 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…This was achieved using three sampling methods (direct visual counts, pan traps, and sticky traps). It has been suggested by several studies that when assessing the abundance and diversity of insect pollinators, the use of multiple sampling methods would provide a better representation of the different types of pollinators in an ecosystem [14,19,[39][40][41][42][43][44]. From our study, diverse pollinator types were recorded.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This was achieved using three sampling methods (direct visual counts, pan traps, and sticky traps). It has been suggested by several studies that when assessing the abundance and diversity of insect pollinators, the use of multiple sampling methods would provide a better representation of the different types of pollinators in an ecosystem [14,19,[39][40][41][42][43][44]. From our study, diverse pollinator types were recorded.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have suggested that an increase in the number of inflorescences may result in an increase in pollinator visits [45][46][47][48]. Pinkeye Purple Hull and Whippoorwill cowpeas produce an average of 49.4 and 56.4 flowers per plant, respectively [19]. These flowers, in addition to those from squash, okra, and watermelon, as well as other floral resources such as nectar and pollen, may have influenced the attraction and abundance of pollinators in the cowpea intercrop.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increase in NPP after mutagenic treatment has also been reported in cowpea (Horn, 2016) and chickpea (Wani, 2011). Increase in NPP has been attributable to an increase in number of flowers in cowpea (Dingha et al 2021). This trait plays a vital role in increased seed yield per plant in cowpea.…”
Section: Number Of Pods Per Plant (Npp) At M 2 and M 3 Generationsmentioning
confidence: 99%